4º Distrito de Porto Alegre: a revitalização de uma região a partir do design estratégico - Mucenic, Paula (Universidade do Vale do Rio dos Sinos, 2014)
The growing competitiveness in today's world challenges cities and territories to deal with increasingly complex variety of issues. The role assumed by places, currently demands a strategic understanding of its goals and its assignments. Therefore, they must be thought of as experiences and products to be consumed by local citizens, tourists and organizations. For that to happen, other tools for the planning of urban revitalization are required. Over the years, numerous cities and regions ended up having non scheduled changes in its main urban plans, being the fourth district of Porto Alegre one of them. Thus, the main goal of this paper, by means of the Strategic Design Metodology is to generate alternatives for the location, considering the blueprint used on the District 22 project, in Barcelona.
Keywords: Design estratégico; Revitalização urbana; 4º Distrito de Porto Alegre; Distrito 22; Trategic design; Urban revitalization; 4º District of Porto Alegre; District 22